Kesalahan Pengginaan Tanda Baca Mahasiswa Pendidikan Bahasa Mandarin Universitas Negeri Jakarta - Zelia, Vanya (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Punctuation marks are signs used in writing to facilitate the understanding of others to what we mean. Errors in the use of punctuation in writing a sentence will have an impact on the meaning of the sentence itself. The purpose of this study was to analyze the use of Chinese punctuation marks, and to find out the factors causing errors in the use of Chinese punctuation marks for students of Mandarin Language Education, State University of Jakarta batch 2015. The theory of punctuation in Mandarin in this study refers to the book《标点符号用法》published by中华人民共和国国家标准2011. This research is a descriptive qualitative research with survey method. Respondents in this study were students of Mandarin Language Education, State University of Jakarta batch 2015.The results of this study indicate that 43.86% use correct Chinese punctuation marks, and 56.14% use Chinese punctuation marks that are not in accordance with their use. The possible factors causes of errors, one of which is the lack of intensity of respondents in using Chinese punctuation marks on Chinese punctuation marks that are not in Indonesian.